Microwave solvothermal synthesis and characterization of manganese-doped ZnO nanoparticles - Wojnarowicz, Jacek; Mukhovskyi, Roman; Pietrzykowska, Elzbieta; Kusnieruk, Sylwia; Mizeracki, Jan; Lojkowski, Witold (Beilstein Journal of Nanotechnology, 2016)
Mn-doped zinc oxide nanoparticles were prepared by using the microwave solvothermal synthesis (MSS) technique. The nanoparticles were produced from a solution of zinc acetate dihydrate and manganese(II) acetate tetrahydrate using ethylene glycol as solvent. The content of Mn2+ in Zn1−xMnxO ranged from 1 to 25 mol %. The following properties of the nanostructures were investigated: skeleton density, specific surface area (SSA), phase purity (XRD), lattice parameters, dopant content, average particle size, crystallite size distribution, morphology. The average particle size of Zn1−xMnxO was determined using Scherrer’s formula, the Nanopowder XRD Processor Demo web application and by converting the specific surface area results. X-ray diffraction of synthesized samples shows a single-phase wurtzite crystal structure of ZnO without any indication of additional phases. Spherical Zn1−xMnxO particles were obtained with monocrystalline structure and average particle sizes from 17 to 30 nm depending on the content of dopant. SEM images showed an impact of the dopant concentration on the morphology of the nanoparticles.
Keywords: manganese-doped zinc oxide nanoparticles; microwave solvothermal synthesis (MSS); characterization techniques of nanomaterials; physical properties of Mn2+-doped ZnO nanoparticles